Unexpected etiology of a pleural empyema in a patient with chronic lymphocytic leukemia (CLL): Capnocytophaga ochracea - Samantha A. Basco; Gregory M. Steele; Andrés F. Henao-Martínez; Carlos Franco-Paredes; Daniel B. Chastain (IDCases, 2020)
Pleural effusions and empyemas caused by Capnocytophaga spp. are uncommon with few cases previously reported. Here, we present the case of a 62-year-old man with untreated chronic lymphocytic leukemia (CLL) complicated by a pleural empyema caused by C. ochracea. The route of acquisition was likely the result of aspiration of C. ochracea coupled with the immune defects associated with untreated CLL.